Artificial Intelligence in urban areas: Proposals for film titles to be used in the classroom - Fernandes, Pedro (Aprender, 2025)
Artificial Intelligence promotes numerous changes in urban territories This article aims to develop a survey of some film titles that allow for debate in the classroom the impacts of AI in urban context. We used IMDb - Internet Movie Database and author personal archive. After the evaluation process, we have selected 7 cinematographic titles. It is concluded that they have the potential to debate relevant topics, such as: replacement of humans by robots, machine learning, health applications ethical issues, data collection and privacy, and also the new forms of urban transport.
Keywords: Artificial Intelligence; Cinema; Teaching-Learning